1994
DOI: 10.1183/09031936.94.07040821
|View full text |Cite
|
Sign up to set email alerts
|

IVOX in ARDS: respiratory effects and serious complications

Abstract: I IV VO OX X i in n A AR RD DS S: : r re es sp pi ir ra at to or ry y e ef ff fe ec ct ts s a an nd d s se er ri io ou us s c co om mp pl li ic ca at ti io on ns s IVOX in ARDS: respiratory effects and serious complications. Y. Gasche, J.A. Romand, R. Prêtre, P.M. Suter. ERS Journals Ltd 1994. ABSTRACT: We describe the beneficial effects of an intravenous oxygenator (IVOX) on ventilatory pressure requirement, and also several severe complications related to its use in a young trauma victim developing severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…For more than two centuries, researchers have evaluated methods to augment gas exchange via the intravenous (IV) route and improve oxygenation during treatment of severe cardiopulmonary disease 1–5. One such method attempted has been the IV injection of gaseous oxygen 6,7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For more than two centuries, researchers have evaluated methods to augment gas exchange via the intravenous (IV) route and improve oxygenation during treatment of severe cardiopulmonary disease 1–5. One such method attempted has been the IV injection of gaseous oxygen 6,7.…”
Section: Introductionmentioning
confidence: 99%
“…For more than two centuries, researchers have evaluated methods to augment gas exchange via the intravenous (IV) route and improve oxygenation during treatment of severe cardiopulmonary disease. 15 One such method attempted has been the IV injection of gaseous oxygen. 6,7 However, subsequent research into the direct IV injection of gaseous oxygen found the technique to be extremely hazardous and frequently fatal due to the formation of large gaseous emboli.…”
Section: Introductionmentioning
confidence: 99%
“…(18) The IVOX is surgically deployed into the inferior or superior vena cava via a femoral or jugular venotomy, by which gas exchange occurs through the hollow fibers driven by a vacuum pump. (19) There is no extracorporeal circulation of blood. Gas exchange is accomplished as the patient's blood flows through the hollow fibers via inlet and outlet gas conduits for oxygen infusion and CO2 elimination.…”
Section: Ivoxmentioning
confidence: 99%